125k views
1 vote
Y=x−1

2x+y=8
If you were to solve the following system using substitution, your new equation would be...

User Mkutyba
by
4.9k points

1 Answer

3 votes

Answer:

2x+ (x-1) = 8

Simplified

3x-1 =8

Explanation:

y=x−1

2x+y=8

Take the first equation and everywhere you see y in the second equation substitute x-1

2x+ (x-1) = 8

You can simplify

2x+x-1 =8

3x-1 =8

If you want to solve

3x-1+1 =8+1

3x= 9

Divide by 3

3x/3 =9/3

x=1

Then solve for y

y = x-1

y = 3-1

y=2

User MyNameIsJob
by
5.6k points